Study of Socio-cultural Support for Stunting in Children of Biak Regency - Hairuddin K; Dian Meliani Yulis; Suprapto Suprapto (Journal of Public Health Sciences, 2026)
Stunting remains a significant public health concern in Indonesia, particularly in Biak Regency, where socio-cultural factors and infant feeding practices influence child growth. This study examined the association between exclusive breastfeeding and socio-cultural support with stunting among children aged 25–59 months in Biak Regency. A cross-sectional analytic design was applied to 35 toddlers from the Ridge Public Health Center and Integrated Services Post. Data were collected via anthropometric measurements and structured questionnaires and analyzed using Fisher’s Exact Test and binary logistic regression. Stunting prevalence was 65.7%, and only 42.9% of children had received exclusive breastfeeding for the first six months of life. In bivariate analysis, none of the exclusively breastfed children and none of those with adequate socio-cultural support were stunted (both p < 0.001). In multivariable analysis, lack of exclusive breastfeeding (No vs Yes) was associated with higher odds of stunting (AOR = 18.0; 95% CI: 2.90–111.60; p < 0.001), and inadequate socio-cultural support (Inadequate vs Adequate) similarly increased the odds (AOR = 18.0; 95% CI: 2.90–111.60; p < 0.001). These results indicate that exclusive breastfeeding and supportive socio-cultural environments are strongly protective against stunting. Given the small sample and wide confidence intervals, findings should be interpreted with caution but highlight the need for culturally sensitive strategies that promote exclusive breastfeeding and address socio-cultural barriers during the first 1,000 days of life.